FAKTOR-FAKTOR YANG MEMPENGARUHI ALOKASI BELANJA MODAL KABUPATEN DAN KOTA DI PROVINSI JAWA TIMUR - Bayu Samodra (EKPI 16 UMY, 2016)
The study aims to determine the factors that affect the allocation of capital expenditures district and cities in the province of East Java. This study use panel data which is a combinacy 29 regency/city over periode 2010-2014, with variable local revenue (PAD), the general allocation fund (DAU), profit sharing fund (DBH), budget financing surplus (SiLPA), and capital expenditures. The analytical method used in this research is regression panel data that is processed by the fixed effect model . The results of this study indicate that the variable revenue (PAD) positive and significant impact on capital expenditures , general allocation fund (DAU) positive and significant impact on capital spending , financing surplus budget (SILPA) positive and significant impact on capital spending , while profit sharing fund (DBH) positive dan significant effect on capital spending. Keywords : locally generated revenue, general allocation fund, revenue sharing, financing surplus budget, capital expenditure